2006
DOI: 10.1016/j.jmb.2006.08.041
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Structural Role of Amino Acid Residues in the Even-numbered Transmembrane α-Helices of the Bovine Mitochondrial Oxoglutarate Carrier

Abstract: The mitochondrial oxoglutarate carrier exchanges cytosolic malate for 2-oxoglutarate from the mitochondrial matrix. Orthologs of the carrier have a high degree of amino acid sequence conservation, meaning that it is impossible to identify residues important for function on the basis of this criterion alone. Therefore, each amino acid residue in the transmembrane alpha-helices H2 and H6 was replaced by a cysteine in a functional mitochondrial oxoglutarate carrier that was otherwise devoid of cysteine residues. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
50
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 39 publications
6
50
0
Order By: Relevance
“…In agreement with the hypothesis that mitochondrial carriers have a similarly located substrate binding site (8) and a conserved transport mechanism, it was found that the bovine 2-oxoglutarate carrier, another member of the mitochondrial carrier family (51)(52)(53), is inactivated by cysteine replacement of the residues corresponding exactly to those characterized here (ORC1, Glu-77, Asn-78, Arg-179, Glu-180, and Arg-275; 2-oxoglutarate carrier, Tyr-94, Thr-95, Arg-190, Ala-191, and Arg-288) (16,54). In the carnitine/ acyl-carnitine carrier, the residues Arg-178, Asp-179, and Arg-275, which correspond to Arg-179, Glu-180, and Arg-275 in ORC1, were also shown to be important for transport (17).…”
Section: Discussionmentioning
confidence: 52%
“…In agreement with the hypothesis that mitochondrial carriers have a similarly located substrate binding site (8) and a conserved transport mechanism, it was found that the bovine 2-oxoglutarate carrier, another member of the mitochondrial carrier family (51)(52)(53), is inactivated by cysteine replacement of the residues corresponding exactly to those characterized here (ORC1, Glu-77, Asn-78, Arg-179, Glu-180, and Arg-275; 2-oxoglutarate carrier, Tyr-94, Thr-95, Arg-190, Ala-191, and Arg-288) (16,54). In the carnitine/ acyl-carnitine carrier, the residues Arg-178, Asp-179, and Arg-275, which correspond to Arg-179, Glu-180, and Arg-275 in ORC1, were also shown to be important for transport (17).…”
Section: Discussionmentioning
confidence: 52%
“…The amount of protein incorporated into liposomes was measured as described (22) and was about 25% of the protein added to the reconstitution mixture. The homology model of Oac1p was built based upon the structure of the bovine ADP/ ATP carrier as described (23,24). An anaerobic Oxoid jar was used to grow yeast strains in anaerobiosis.…”
Section: Methodsmentioning
confidence: 99%
“…Sequence homology shows that almost every MCF member contains a Lys or an Arg at the position equivalent to MFT Arg-288 (9). This (K/R) residue is required for transport in every MCF protein in which it has been mutated (11,33,34); we also showed MFT Arg-288 to be required for folate transport (Fig. 5B).…”
Section: Discussionmentioning
confidence: 54%
“…Although almost all MCF transporters carry a (D/E) at MFT 142, we found that the MFT absolutely cannot function with a (D/E) residue at this position. In addition to the Trp substitution definitive of this subfamily, all P(I/L)W transporters contain a Gly at MFT 91, whereas the closely related MCF nucleotide transporters and several other MCF proteins require a Lys or an Arg at this position for function (11,33,34). Gly-91 was predicted to be very close to Trp-142 at the base of the cavity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation